Preparation of surface-modified electrode of copper(ii) oxide mixed with the molecularly imprinted polymer for enhancement of melamine detection with photoelectrochemical technique - Dalawan Limthin; Piyawan Leepheng; Benchapol Tunhoo; Korakot Onlaor; Annop Klamchuen; Darinee Phromyothin; Thutiyaporn Thiwawong (RSC Advances, 2023)
, with a linear range of 5.0-75.0 nM and a limit of detection of 2.45 nM. Moreover, real samples of various kinds of milk were applied to evaluate the sensing response of the prepared CuO/MIP electrode. The modified CuO/MIP electrodes could be reused seven times with good reproducibility and high selectivity for melamine detection.
Keywords: Melamine detection and toxicity; Advanced Nanomaterials in Catalysis; Advanced biosensing and bioanalysis techniques